Hybrid repair of acute type B dissection with aberrant right subclavian artery and bicarotid trunk - Peter S. Downey, MD; Axel Thors, DO; Phillip Johnson, MD; Kamal Gupta, MD; William J. Wallisch, MD; Omar Almoghrabi, MD; Gregory F. Muehlebach, MD; George L. Zorn, III, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Patients with type B aortic dissection (TBAD) often present as an emergency. Operative repair of TBAD can be indicated for selected patients in the setting of hemodynamic instability or rupture. Thoracic endovascular aortic repair of TBAD has achieved significant popularity. Variant aortic arch anatomy can present a significant clinical challenge in patients with an inadequate proximal landing zone for thoracic endovascular aortic repair. A three-stage, hybrid aortic arch debranching and endovascular repair of a ruptured TBAD in a patient with a bicarotid trunk and an aberrant right subclavian artery was successfully performed using a unique technical approach.